Aramid fiber recovery from waste composite by pyrolysis - Sebe, Emese; Kállay, András Arnold (Multidiszciplinaris Tudomanyok, 2023)
Due to their outstanding mechanical properties and temperature resistance, aromatic polyamides are widely used for reinforcement in composite materials. The high consumption leads to an increasing waste generation. The recycling of composites requires a complex process, therefore the investigation of aramid fiber recovery is still in the middle of attention. In this study, the pyrolytic behavior of a waste aramid composite was investigated. Then laboratory-scale pyrolysis experiments were performed in a tubular reactor at 400 °C.